Magnetic control adjustable heat phase change material for electromagnetic wave absorption and preparation method thereof

By using the planar coil magnetic field in electromagnetic wave absorbing materials to adjust the magnetic particle structure and thermoplastic paraffin phase transformation, combined with expanded graphite, the problem of difficult adjustment of the wave absorption performance of traditional materials is solved, and dynamic optimization and efficient wave absorption performance are achieved, suitable for multi-band and high temperature environment.

CN119275597APending Publication Date: 2025-01-07STATE GRID CHONGQING ELECTRIC POWER COMPANY MARKETING SERVICE CENTER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorbing materials are difficult to adjust their absorbing performance after curing and forming, and cannot meet the demand for dynamic adjustment in actual applications.

Method used

By using the magnetic field generated by the planar coil during the material heating and melting stage, changing the chain structure arrangement of magnetic particles, combining the phase change behavior of thermoplastic paraffin, a magnetron adjustable thermal phase change material was prepared, using nano-Fe@flake carbonyl iron powder. As magnetically enhanced particles, expanded graphite is added to enhance thermal stability and shape memory functions.

Benefits of technology

The material has realized the multi-band wave absorption capability and dynamic response capability. It can re-drive the distribution of magnetic particles through high temperature conditions and magnetic fields during use, optimize the wave absorption performance, and is suitable for electromagnetic stealth, radar wave absorption and other fields, with a high level of Industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275597A_ABST
    Figure CN119275597A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic control adjustable heat phase change material for electromagnetic wave absorption and a preparation method thereof, and the magnetic control adjustable heat phase change material comprises the following raw materials in parts by mass: a thermoplastic paraffin matrix, and magnetic composite particles and expanded graphite which are distributed in the thermoplastic paraffin matrix, the magnetic composite particles are prepared by depositing nano Fe on the surface of flaky carbonyl iron powder through an oxidation-reduction method. The composite material is cast on a substrate with a planar coil, and different magnetic field modes are formed by adjusting the current direction of the planar coil when the material is heated and melted so as to change the chained arrangement mode of the magnetic particles, so that the wave-absorbing performance is optimized. By changing the heating condition and the magnetic field direction, the microstructure of the material is subjected to phase change driven reconstruction, and the material is endowed with multi-band wave-absorbing capacity and dynamic response characteristic. The invention combines the dual characteristics of thermal phase change and magnetic response, and is especially suitable for the field of intelligent stealth devices and electromagnetic wave protection requiring variable wave absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials applied to intelligent devices, and in particular to a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption, a preparation method thereof and a preparation method thereof. Background Art

[0002] The present invention provides a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption and a preparation method thereof, which is prepared by dispersing micro-nano-scale magnetic particles into a thermoplastic paraffin matrix and combining with expanded graphite. Under the action of the magnetic field generated by a planar coil, the magnetic particles form a chain structure parallel to the direction of the magnetic field through the phase change behavior (melting and solidification process) of the thermoplastic matrix, thereby changing the microstructural characteristics of the material. The present invention combines the change in the direction of the magnetic field during the heating and melting stage of the material, and dynamically optimizes the distribution of magnetic particles during the phase change process of the thermoplastic matrix to form a specific chain structure, which gives the material multi-band wave absorption ability after cooling and solidification. The performance of traditional electromagnetic wave absorption materials is difficult to adjust once solidified and cannot meet the demand for dynamic adjustment of wave absorption performance in practical applications. The present invention uses nano Fe@ flake carbonyl iron powder as magnetic enhancement particles, and uses the magnetic field generated by the planar coil compounded under the material to achieve dynamic optimization of the electromagnetic wave absorption performance of the material. At the same time, by using expanded graphite as a shape stabilizer, the thermal stability and shape memory function of the material are further improved, so that it can still maintain excellent wave absorption performance when the external environment changes. The present invention can change the arrangement of magnetic particles in the phase change process through the magnetic field generated by the planar coil to optimize the performance, giving the material dynamic response ability to wave absorption performance in different frequency bands. This feature makes the magnetically controlled adjustable thermal phase change material of the present invention have a wide range of application prospects in the fields of electromagnetic wave absorption, stealth materials and related intelligent wave absorbing devices. Summary of the invention

[0003] In view of this, the present invention provides a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption and a preparation method thereof, which optimizes the dynamic performance of the composite material by combining the thermally induced phase change characteristics of thermoplastic paraffin wax and the magneto-induced effect of magnetic composite particles. The present invention also provides a preparation method of the magnetically controlled adjustable thermal phase change material.

[0004] To achieve the above object, the present invention provides the following technical solution: a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption, comprising the following raw material components in mass fractions: The invention comprises a thermoplastic paraffin matrix, magnetic composite particles and expanded graphite distributed in the thermoplastic paraffin matrix, wherein the magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder by a redox method; the composite material is cast on a substrate with a planar coil, and when the material is heated and melted, the current direction of the planar coil is adjusted to form different magnetic field modes to change the chain arrangement of the magnetic particles, thereby optimizing the wave absorption performance. The magnetically controlled adjustable thermal phase change material provided by the invention comprises a thermoplastic paraffin matrix, magnetic composite particles and expanded graphite distributed in the matrix, wherein the magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder by a redox method. The invention adopts magnetic composite particles as wave absorption enhancement particles, and through the shape stabilization effect of the expanded graphite, in the melting-solidification process of the thermoplastic paraffin, the magnetic field generated by the planar coil drives the chain structure of the magnetic particles Arrangement, thereby dynamically adjusting the electromagnetic wave absorption characteristics of the composite material. When preparing the material, nano Fe@ flake carbonyl iron powder (CIP) is prepared as magnetic composite particles, added to liquid thermoplastic paraffin, and expanded graphite is added at the same time. After mechanical stirring, the mixture is poured into a mold and cooled and solidified under the action of a uniform magnetic field. The magnetic composite particles can form a chain structure consistent with the direction of the magnetic field under the action of the magnetic field, giving the composite material excellent electromagnetic wave absorption performance, and the wave absorption characteristics can be dynamically optimized through the magnetic field. The magnetically controlled adjustable thermal phase change material of the present invention can not only design its internal structure during the curing and molding process, but also can re-drive the reconstruction of the distribution state of the magnetic particles through the high temperature conditions and the magnetic field generated by the planar coil during use, so as to further optimize the wave absorption performance. The material has a significant electromagnetic wave absorption effect in a specific frequency band, and has good thermal stability and shape stability.

[0005] A method for preparing a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption comprises the following steps: Step 1: prepare magnetic composite particles, add flaky carbonyl iron powder and dispersant into ferrous sulfate solution, stir evenly, slowly add sodium borohydride solution to carry out reduction reaction, and obtain nano-Fe@flaky CIP; Step 2: Evenly stir the magnetic composite particles and liquid thermoplastic paraffin; Step 3: Add expanded graphite, mix evenly, and pour into the mold; Step 4: Place the mold on a substrate with a planar coil, and form different magnetic field modes by adjusting the current direction of the planar coil during the material heating and melting stage, and obtain a composite material with magnetically controlled adjustable wave absorption performance after cooling and solidification.

[0006] Preferably, the magnetic field pattern includes: Mode 1: The planar coil generates a full N-pole magnetic field; Mode 2: The planar coil generates a magnetic field with N poles and S poles arranged in rows and intervals; Mode 3: The planar coil generates a magnetic field with N poles and S poles arranged in blocks and at intervals.

[0007] Preferably, the material composition includes 40-50 parts of paraffin wax, 30-40 parts of nano-Fe@ flake CIP, and 10-20 parts of expanded graphite.

[0008] Preferably, the curing time in step 4 is 5-10 minutes, and the melting temperature ranges from 50-80°C.

[0009] The beneficial effects of the present invention are as follows: the present invention realizes dynamic optimization of the material's wave absorption performance through phase change-driven magnetic particle reconstruction. Furthermore, in the material heating and melting stage, different magnetic field modes are formed by adjusting the current direction of the planar coil, inducing the magnetic composite particles to be arranged into a chain structure with all N poles, N poles and S poles spaced in rows or blocks, thereby optimizing the electromagnetic wave absorption performance. The addition of expanded graphite improves the shape stability of the material and prevents the material from changing shape during the thermal phase change process. The magnetically controlled adjustable thermal phase change material of the present invention has excellent performance in wave absorption performance, thermal stability and dynamic response capability, and is suitable for electromagnetic stealth, radar absorption, wireless communications and other fields, and has high industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a schematic diagram of the preparation process of the present invention.

[0011] Figure 2 It is a schematic diagram of the thermoplastic composite material of Example 1 of the present invention at high temperature and different magnetic field modes.

[0012] Figure 3 It is a schematic diagram of the wave absorption test experiment table of the present invention. DETAILED DESCRIPTION

[0013] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0014] A magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption, comprising the following raw material components in parts by weight: The invention comprises a thermoplastic paraffin matrix, magnetic composite particles and expanded graphite distributed in the thermoplastic paraffin matrix, wherein the magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder by a redox method; the composite material is cast on a substrate with a planar coil, and when the material is heated and melted, the current direction of the planar coil is adjusted to form different magnetic field modes to change the chain arrangement of the magnetic particles, thereby optimizing the wave absorption performance. The magnetically controlled adjustable thermal phase change material provided by the invention comprises a thermoplastic paraffin matrix, magnetic composite particles and expanded graphite distributed in the matrix, wherein the magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder by a redox method. The invention adopts magnetic composite particles as wave absorption enhancement particles, and through the shape stabilization effect of the expanded graphite, in the melting-solidification process of the thermoplastic paraffin, the magnetic field generated by the planar coil drives the chain structure of the magnetic particles Arrangement, thereby dynamically adjusting the electromagnetic wave absorption characteristics of the composite material. When preparing the material, nano Fe@ flake carbonyl iron powder (CIP) is prepared as magnetic composite particles, added to liquid thermoplastic paraffin, and expanded graphite is added at the same time. After mechanical stirring, the mixture is poured into a mold and cooled and solidified under the action of a uniform magnetic field. The magnetic composite particles can form a chain structure consistent with the direction of the magnetic field under the action of the magnetic field, giving the composite material excellent electromagnetic wave absorption performance, and the wave absorption characteristics can be dynamically optimized through the magnetic field. The magnetically controlled adjustable thermal phase change material of the present invention can not only design its internal structure during the curing and molding process, but also can re-drive the reconstruction of the distribution state of the magnetic particles through the high temperature conditions and the magnetic field generated by the planar coil during use, so as to further optimize the wave absorption performance. The material has a significant electromagnetic wave absorption effect in a specific frequency band, and has good thermal stability and shape stability.

[0015] A method for preparing a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption comprises the following steps: Step 1: prepare magnetic composite particles, add flaky carbonyl iron powder and dispersant into ferrous sulfate solution, stir evenly, slowly add sodium borohydride solution to carry out reduction reaction, and obtain nano-Fe@flaky CIP; Step 2: Evenly stir the magnetic composite particles and liquid thermoplastic paraffin; Step 3: Add expanded graphite, mix evenly, and pour into the mold; Step 4: Place the mold on a substrate with a planar coil, and form different magnetic field modes by adjusting the current direction of the planar coil during the material heating and melting stage, and obtain a composite material with magnetically controlled adjustable wave absorption performance after cooling and solidification.

[0016] Furthermore, the magnetic field pattern includes: Mode 1: The planar coil generates a full N-pole magnetic field; Mode 2: The planar coil generates a magnetic field with N poles and S poles arranged in rows and intervals; Mode 3: Planar coil generates magnetic field with N poles and S poles arranged in blocks Furthermore, the material composition includes 40-50 parts of paraffin wax, 30-40 parts of nano-Fe@ flake CIP, and 10-20 parts of expanded graphite.

[0017] Furthermore, the curing time of step 4 is 5-10 minutes, and the melting temperature ranges from 50-80°C.

[0018] Embodiment 1: A magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption includes a thermoplastic paraffin matrix, magnetic composite particles distributed in the matrix, and expanded graphite. The magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder (CIP) by a redox method. The thermoplastic phase change composite material includes the following components by weight: 50 parts of paraffin, 40 parts of nano-Fe@flaky CIP, and 10 parts of expanded graphite.

[0019] In this embodiment, the method for preparing the magnetic composite particles comprises the following steps: Magnetic particles (flaky carbonyl iron powder) and dispersant (polyvinyl pyrrolidone) are added to ferrous sulfate solution, and after mechanical stirring, sodium borohydride solution is slowly added as a reducing agent to control the magnetic particles generated by the reaction to be uniformly deposited on the surface of the flaky CIP. After the reaction is completed, the magnetic solid is separated from the reaction solution by a magnet, and repeatedly washed with deionized water and anhydrous ethanol to remove impurities. Finally, it is dried in a vacuum drying oven at 80°C for more than 6 hours to obtain nano-Fe@flaky CIP with a particle size of less than 5 microns.

[0020] During material preparation, the magnetic composite particles prepared above are mechanically stirred with liquid paraffin for 30 minutes, expanded graphite is added, and the mixture is poured into a mold after stirring evenly. During the phase change stage of matrix melting, by adjusting the current direction of the planar coil, the magnetic particles are induced to freely arrange in the liquid matrix to form a dynamic chain structure. As the material cools and solidifies, the chain structure is fixed, and finally a composite material with significant wave absorbing performance is formed. The reflection loss peak value of the thermoplastic composite material prepared in this embodiment is -28.80dB, and the effective wave absorbing bandwidth is 5.76GHz.

[0021] Comparing the microwave absorption effect of the thermoplastic phase change composite material prepared in the above embodiment under high temperature and different magnetic field modes, the results are shown in the attached Figure 3 As shown: According to the attached Figure 3It can be seen that the present invention utilizes nano-Fe@sheet CIP / expanded graphite / planar coil to achieve variable performance characteristics of paraffin composite materials. For example, after magnetron adjustment, the thermoplastic composite material of Example 1, when the magnetic field configuration is as shown in mode three, has a reflection loss peak value reduced by 47.6% and an effective absorption bandwidth increased by 44% compared to when no magnetic field is applied.

[0022] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption, characterized in that: The invention comprises the following raw material compositions in parts by mass: a thermoplastic paraffin matrix, magnetic composite particles and expanded graphite distributed in the thermoplastic paraffin matrix, wherein the magnetic composite particles are prepared by depositing nano-Fe on the surface of flaky carbonyl iron powder by a redox method; and different magnetic field modes are formed by casting the composite material on a substrate with a planar coil, and adjusting the current direction of the planar coil when heating and melting the material, so as to change the chain arrangement of the magnetic particles, thereby optimizing the wave absorbing performance.

2. A method for preparing a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption, characterized in that , including the following steps: Step 1: prepare magnetic composite particles, add flaky carbonyl iron powder and dispersant into ferrous sulfate solution, stir evenly, slowly add sodium borohydride solution to carry out reduction reaction, and obtain nano-Fe@flaky CIP; Step 2: Evenly stir the magnetic composite particles and liquid thermoplastic paraffin; Step 3: Add expanded graphite, mix evenly, and pour into the mold; Step 4: Place the mold on a substrate with a planar coil, and form different magnetic field modes by adjusting the current direction of the planar coil during the material heating and melting stage, and obtain a composite material with magnetically controlled adjustable wave absorption performance after cooling and solidification.

3. The method for preparing a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption according to claim 2, characterized in that: The magnetic field modes include: Mode 1: The planar coil generates a full N-pole magnetic field; Mode 2: The planar coil generates a magnetic field with N poles and S poles arranged in rows and intervals; Mode 3: The planar coil generates a magnetic field with N poles and S poles arranged in blocks and at intervals.

4. The method for preparing a magnetically controlled adjustable thermal phase change material for electromagnetic wave absorption according to claim 2, characterized in that: The material composition comprises 40-50 parts of paraffin wax, 30-40 parts of nano-Fe@ flake CIP and 10-20 parts of expanded graphite.

5. The method for preparing a magnetically controlled tunable thermal phase change material for electromagnetic wave absorption according to claim 2, characterized in that: The curing time of step 4 is 5-10 minutes, and the melting temperature range is 50-80°C.